Територія і кордон як фактори формування етнічної ідентичності (за матеріалами досліджень прикордонних територій Брянської області) - Григор’єва, Р. (Народна творчість та етнографія, 2010)
В статье на основе современного исследования, проведённого среди населения Брянской области России, которое проживает на пограничье с Беларусью и Украиной, отражён процесс формирования этнической идентичности у местных подростков (16–18 лет). Также проанализирован ряд идентичных критериев, факторов исторического взаимодействия трёх восточнославянских народов в сфере образования, культуры, языка, конфессиональной принадлежности и т. п. Based on the modern investigation amongst the Russian Briansk Oblast people living on the frontier with Byelorussia and Ukraine there is an elucidation of the ethnical identity formative process amidst the local teenagers (16–18-year-old). Moreover analysed is a number of the identical criteria and factors of the historical interrelations of the three Eastern Slavonic nations in the fields of education, culture, language, confession, etc.